Genotype environment interactions for cyanogenic potential in cassava - Bokanga, M.; Ekanayake, I.J.; Dixon, A.; Porto, M. (International Society for Horticultural Science, 1994)
The distribution of the cyanogenic potential in cassava germplasm has been found to be a continuum from very low values to high levels. Within the same genotype, the cyanogenic potential is affected by the planting season; it is low when planted at the beginning of the rainy season, and high when planted at the end of the rainy season. Water stress is known to increase the cyanogenic potential. Recent findings indicate that the effects of water stress on cyanogenic potential are more complex than originally thought. A high ground water table with an associated low water stress to the developing cassava roots does not necessarily lead to lower cyanogenic potential. Excess water stress created by an above ground water table leads to higher cyanogenic potential. The location effect on cyanogenic potential is very pronounced. The cyanogenic potential of a genotype can increase up to five-fold when planted in a different location. The genotype-environment interactions are less pronounced but significant; some genotypes maintain the same cyanogenic potential ranking when planted in various agroecological zones, even though the absolute values of cyanogenic potential may be increased or decreased. These effects of the environment on cassava cyanogenic potential are explained using available knowledge on biosynthesis, regulation and translocation of cyanogenic glucosides.